PENINGKATAN HASIL BELAJAR SISWA MELALUI PBL BERBASIS MEDIA AUDIO VISUAL DIKELAS VI SDN PANDEAN LAMPER04 SEMARANG - Achmad Asrori; Ida Dwijayanti; Fenny Roshayanti (Journal Prakarsa Paedagogia, 2023)
The purpose of this study was to find out that the problem-based learning method on audio-visual media can improve the learning outcomes of class VI students at SD Negeri Pandean Lamper 04. Information on the material being taught is obtained from tests at the end of each cycle. Meanwhile, with the help of the observation form at PPL I, information was obtained about student performance and the process of implementing teacher learning. The results showed that learning through a problem-based learning model or Problem Based Learning with audio-visual media can improve student learning outcomes. The average percentage value of students in the pre-cycle period was 40% and in the first cycle period it increased to 65% for the completeness score and 85% for cycle II. From the results of this study it can be concluded that by applying the Problem Based Learning learning model can improve student learning outcomes